ORGANISASI ISLAM DAN PERANNYA TERHADAP PENDIDIKAN ISLAM DI INDONESIA - Choirunniswah Choirunniswah (Ta'dib: Jurnal Pendidikan Islam, 2013)
The emergence of Islamic organizations in Indonesia is much more caused by the encouragement started with the growing sense of patriotism and nationalism as well as the response to the imbalances that exists among the people of Indonesia in the 19th century which experienced the total declination as a result of the political exploitation of the Dutch East Indies colonial government. The first step to be realized is the awareness to be involved in the organizations. through those organizations, moslem people will be in turn to have a big role in the struggle for independence. Those people with persistence and self-sacrificing spirit and soul as well as treasures, had died as a hero. This paper will discuss on the role of these organizations in the field of education.